The Effect of Packaging Design on Impulsive Buying - Cahyorini, Astri; Rusfian, Effy Zalfiana (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2012)
he packaging design’s important role as a means of marketing communication is growing. This research examines the effect of Monggo size 40 grams’ packaging design on impulsive buying in South Jakarta and also examines which one among the dimensions in packaging design (graphic design, structure design, and product information) has the biggest effect on impulsive buying. This research uses the quantitative approach to explain the connection between the two variables. The data was collected through questionnaires filled out by impulsive buyers of Monggo size 40 grams in South Jakarta. A total of 100 respondents are examined using the purposive sampling technique. The result of the research shows that the packaging design affects impulsive buying at a rate of 38.0% and the packaging design dimension that results in impulsive buying is graphic design. We may conclude that Monggo’s management needs to review the brand’s packaging design. As the management is yet to utilize other communicating tools such as advertisements to support marketing communication, the packaging design becomes more crucial in boosting sales. The research also finds that customers have a great liking for the brand name ‘Monggo’, as it is a very distinctly traditional name that is not only appealing but also noticeable among the current brands